Results of a prospective, mixed methods study to assess feasibility, acceptability and effectiveness of TRIumPH (Treatment and Recovery In PsycHosis): an integrated care pathway for psychosis, compared to usual treatment. Issue 4 (29th April 2020) - Rathod, Shanaya; Thorne, Kerensa; Graves, Elizabeth; Phiri, Peter; Asher, Carolyn; Griffiths, Alison; Read, Tracy; Kingdon, David
Abstract : Objectives: To evaluate whether a newly developed care pathway, Treatment and Recovery In PsycHosis (TRIumPH), is feasible, acceptable and effective in meeting National Institute of Health and Care Excellence (NICE) quality standards in a timely manner. Methods: This is a pragmatic, non-randomised, prospective, mixed methods study comparing an implementation (TRIumPH) and comparator site (not implementing TRIumPH) across three cohorts to assess feasibility, acceptability and effectiveness of the integrated pathway. Setting: Early intervention in psychosis (EIP) services at two National Health Service organisations in South of England. Participants: All patients accepted into EIP services between 1 June 2014 and 31 May 2017 were each followed up for 1 year within their respective cohorts. Methodology: Quantitative data consisted of routinely collected clinical data retrieved from patient records to assess whether the implementation of TRIumPH achieved better concordance to NICE standards. These included time to access services, physical health assessments, clinical outcomes based timeliness of delivery and acute data. The controlled trial has evaluated the effect of TRIumPH (Intervention) with Care As Usual (Comparator). Qualitative measures consisted of questionnaires, interviews and focus groups to assess acceptability and satisfaction. Outcome measures were compared within the baseline, year 1 and year 2 cohorts and between the two sites. Quantitative data were statistically analysed by comparing means and proportions. Results: Time to assessment improved in the implementation site and remained within the target in comparator site. Meeting of quality standards increased substantially in the implementation site but was more variable and reached lower levels in the comparator site especially for physical health standards. Cognitive therapy for psychosis, family intervention and carer and employment support were all offered to a greater extent in the implementation site and uptake increased over the period. Conclusions: Pathway implementation generally led to greater improvements in achievement of access and quality standards compared with comparator site. Trial registration number: UK Clinical Research Network Portfolio (19187)